Hepatocyte miR‐33a mediates mitochondrial dysfunction and hepatosteatosis by suppressing NDUFA5. Issue 12 (16th October 2018) - Nie, Hezhongrong; Yu, Xiaohong; He, Haihong; Zhou, Lintao; Li, Qing; Song, Chunli; Wang, Damin; Ren, Tingyu; Chen, Zeyan; Huang, Hanlian; Dai, Xiaoyan; Zhou, Yiwen
Abstract: Emerging evidence suggests that microRNAs (miRNAs) are essential for metabolic haemostasis of liver tissues. Among them, miR‐33a is supposed to modulate the cholesterol export and fatty acid oxidation, but whether miR‐33a involves in the process of fatty liver disease is unclear. To disclose the hypothesis, we utilized miR‐33a mimic and antisense to explore their effects in primary hepatocytes or high‐fat diet (HFD)‐fed mice. Treatment with palmitic acid (PA) or HFD significantly increased the expression of miR‐33a in hepatocytes or liver tissues. In primary hepatocytes, miR‐33a mimic decreased mitochondrial function, including reduction of ATP production and oxygen consumption, whereas miR‐33a inhibition protected PA‐induced mitochondrial dysfunction. Interestingly, miR‐33a selectively suppressed mitochondrial complex I activity and protein expression, but not other complexes. Through bioinformatics prediction, we found miR‐33a directly targeted on the 3′‐UTR of NDUFA5 . Dual‐luciferase reporter analysis further confirmed the direct suppression of miR‐33a on NDUFA5 expression. More importantly, administration of miR‐33a antisense could effectively restore HFD‐induced mitochondrial dysfunction through up‐regulation of NDUFA5 levels. Mice treated with miR‐33a antisense also exhibited improved liver function and structural disorders under obese status. Taken together, miR‐33a was an important mediator of hepatocyte mitochondrial function, and the therapeutic benefits implied miR‐33a antisense had the potential clinical application in combating the fatty liver disease.